Easy Advancement of a Large-Profile Microcatheter (Excelsior XT27™) by Parallel Use of Two Microguidewires For Stent Delivery - Yudhi Adrianto; Ku Hyun Yang; Hae-Won Koo; Wonhyoung Park; Jung Cheol Park; Deok Hee Lee (Neurointervention, 2016)
PurposeIn the endovascular treatment of cerebral aneurysms, navigating a large-bore microcatheter for delivery of an open-cell stent can be challenging, especially in wide-necked bifurcation aneurysms. We were able to overcome this difficulty by parallel use of two microguidewires through the stent-delivery microcatheter.Materials and MethodsFrom December 2014 to April 2015, we treated 15 patients with wide-necked bifurcation aneurysms. For stent delivery, we used a 300-cm 0.014-in microguidewire (Transend), which was placed into the target branch using an exchange technique. A 0.027-in microcatheter (Excelsior XT-27), which was designed for the stent, was advanced over the exchange microguidewire. If we had trouble in advancing the microcatheter over the exchange microguidewire, we inserted a regular microguidewire (Traxcess), into the microcatheter lumen in a parallel fashion. We also analyzed the mechanism underlying microcatheter positioning failure and the success rate of the 'parallel-wire technique'.ResultsAmong the 15 cases, we faced with navigation difficulty in five patients. In those five cases, we could advance the microcatheter successfully by applying the parallel-wire technique. There were no procedure-related complications.ConclusionSimply by using another microguidewire together with pre-existing microguidewire in a parallel fashion, the stent-delivery microcatheter can be easily navigated into the target location in case of any advancement difficulty.